INCREASE OF DURABILITY OF BEARING ROLLERS OF MNLZ - Ju. A. Samojlovich; V. I. Timoshpolski; V. A. Goijainov; S. M. Kabishov (Литьë и металлургия, 2008)
The mechanisms of occurrence of thermal stresses and deformations in bearing rollers of machines of the slugs continuous casting and are investigated and new methods of increase of their durability are offered.